The woman beyond the attic the V. C. Andrews story - Neiderman, Andrew 1940- (Gallery Books, 2022)
"This celebration of the woman who took us to the heights of a secluded attic and the depths of our own dark psyches reveals an intimate portrait of the famously private V.C. Andrews. Best known for her internationally, multi-million-copy bestselling novel Flowers in the Attic, Cleo Virginia Andrews lived a fascinating life. Born to modest means, she came of age in the American South during the Great Depression and faced a series of increasingly challenging health issues. Yet, once she rose to international literary fame, she prided herself on her intense privacy. Now, The Woman Beyond the Attic aims to connect her personal life with the public novels for which she was famous. Based on Virginia's own letters, and interviews with her dearest family members, her long-term ghostwriter Andrew Neiderman tells Virginia's full story for the first time. Featuring family photos, personal letters, a partial manuscript for an unpublished novel, and more, The Woman Beyond the Attic is perfect for V.C. Andrews fans who pick up every new novel or for fans hoping to return to the favorite novelist of their adolescence. Eye-opening and intimate, The Woman Beyond the Attic is for anyone hoping to learn more about the enigmatic woman behind one of the most important novels of the 20th century"--
Includes bibliographical references (pages [251]-252) and index
Keywords: Andrews, Virginia C. -- 1923-1986; Andrews, V. C. / (Virginia C.); Authors, American / 20th century / Biography; Women authors, American / 20th century / Biography; Novelists, American / 20th century / Biography; Women novelists, American / 20th century / Biography; Authors with disabilities / Biography; Écrivains américains / 20e siècle / Biographies; Écrivaines américaines / 20e siècle / Biographies; Romanciers américains / 20e siècle / Biographies; Romancières américaines / 20e siècle / Biographies; Écrivains handicapés / Biographies; BIOGRAPHY & AUTOBIOGRAPHY / Literary Figures; BIOGRAPHY & AUTOBIOGRAPHY / Women; LITERARY CRITICISM / Women Authors; Authors, American; Authors with disabilities; Novelists, American; Women authors, American; Women novelists, American; 1900-1999; Biography; Biographies; Biografie